Specialized intensive inpatient rehabilitation is crucial and time-sensitive for functional recovery from disorders of consciousness - Zhang, Bei; O'Brien, Katherine; Woo, Jean; Chi, Bradley; Reeh, Colton; Li, Sheng; Kothari, Sunil (Frontiers in Neurology, 2023)
Background Disorders of consciousness (DoCs) after severe brain injury are considered to be conditions with dire prognosis. Despite the accumulating evidence, inpatient rehabilitation is often denied by payers referring to the Medicare/Medicaid criteria, under the assumption that such patients will not “actively” participate in therapy or make “measurable improvements.” Objective This study aimed to report on the effectiveness and efficiency of a specialized inpatient DoC rehabilitation program based on measurable clinical parameters. Methods A retrospective cohort study was conducted. The cohort comprised 137 patients with DoC admitted to a specialized acute inpatient rehabilitation program between January 2014 and October 2018. Patients were categorized as having been admitted at the acute stage (<=28 days post-injury), subacute stage (29–365 days following a traumatic brain injury (TBI) or 29–90 days following a non-TBI), or chronic stage (>365 days following a TBI or >90 days following a non-TBI). Outcomes included changes in level of consciousness (based on the Coma Recovery Scale–Revised (CRS-R), while also acknowledging scenarios beyond those captured by the CRS-R via Individualized Qualitative Behavioral Assessment and team consensus); Functional Independence Measure (FIM) levels; achievements in decannulation and initiation of oral diet; and time to those achievements. Results The rates of emergence from a minimally conscious state were 90, 62, and 18% among patients admitted at the acute, subacute, and chronic stages, respectively. Among patients who emerged, 100, 85, and 67%, respectively, had measurable FIM scores. Approximately 60 and 20% of patients at the acute and subacute stages, respectively, required moderate assistance or less in transfer/communication/eating/grooming/upper body dressing by the time of discharge from Phase I admission. The decannulation rates were 94, 67, and 17%. The oral diet initiation rates were 70, 23, and 6%. The time to reach these achievements lengthened as chronicity increased. There was a weak positive correlation (rs = 0.308) in the case of decannulation and a strong positive correlation (rs = 0.606, both p < 0.01) in the case of oral diet between days since injury on admission and days to the achievement after admission. Patients with TBI and hypoxic brain injury had comparable recovery rates when admitted at the acute and subacute stages. Conclusion Specialized intensive inpatient rehabilitation is crucial and time-sensitive for functional recovery from DoC caused by TBI and hypoxic–ischemic brain injury. Specific goals and different outcome measures need to be developed to appraise the benefits of acute inpatient rehabilitation for DoC.